REFLEKSI KEMUNDURAN DINASTI UMAYYAH DAN DINASTI ABASIYYAH - Ahmad Fananie; Nanang Mulyana; Muhammad Azka Maulana (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2021)
The reign of the Umayyad and Abbasid caliphate has incised Islamic civilization in its time. The progress of Islamic civilization cannot be ignored from the role of the caliphs of the Umayyad and Abbasid dynasties. Every government in the era of the two dynasties experienced a period of growth, glory and fall. This study analyzes the causes of the fall of the Umayyad and Abbasid dynasties; ranging from socio-political aspects, Islamic values, to leadership principles based on the example of the Prophet Muhammad. This research method uses a qualitative approach with discussion and analysis based on Islamic literature sources, such as books, journals and others. Some of the findings in this study include: the position of the caliphs of the Umayyad and Abbasid dynasties has an important role, the values ??of Islamic government refer to the example of the leadership of the Prophet Muhammad, and the role of the leaders of the two dynasties (Umayyad and Abbasid) greatly determines the success and decline of the two dynasties.